2015
DOI: 10.1177/0269216315615483
|View full text |Cite
|
Sign up to set email alerts
|

What are the views of hospital-based generalist palliative care professionals on what facilitates or hinders collaboration with in-patient specialist palliative care teams? A systematically constructed narrative synthesis

Abstract: Fuller integration of specialist palliative care services, timely sharing of information and mutual respect increase generalists' perceptions of effective collaboration. Further research is needed regarding the experiences of non-physician and non-nursing professionals as their views were either not included or not explicitly reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 73 publications
(541 reference statements)
2
83
0
3
Order By: Relevance
“…A study of community palliative care nurse and physician providers found that developing strong relationships facilitates perceptions of cohesion and contributes to wards’ ability to do their own work, this study confirms similar patterns of relating occur in the inpatient setting with social workers as well [49]. Additionally, similar to previous studies, relationships and collaboration were enhanced by co-location [12, 21, 49, 50]. The similarities between these results and existing knowledge, which primarily stems from studies of nurses and physicians, are noteworthy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A study of community palliative care nurse and physician providers found that developing strong relationships facilitates perceptions of cohesion and contributes to wards’ ability to do their own work, this study confirms similar patterns of relating occur in the inpatient setting with social workers as well [49]. Additionally, similar to previous studies, relationships and collaboration were enhanced by co-location [12, 21, 49, 50]. The similarities between these results and existing knowledge, which primarily stems from studies of nurses and physicians, are noteworthy.…”
Section: Discussionsupporting
confidence: 86%
“…For social work collaboration to be successful it is important to understand what social workers view as collaborative. Very little is known about ward social workers’ perceptions of collaborating with palliative care social workers [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Nurses are in a pivotal position to strengthen partnership working between providers across range of care settings, with positive outcomes for patients (Firn et al, 2016). However, nursing needs to continue to adapt and respond to the changing needs of the patients and their families in a rapidly changing healthcare environment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the split between generalist and specialist palliative care can be problematic, with continuing debate about remit, roles and boundaries (Firn et al, 2016) (Gardiner et al, 2012). Although specialists in palliative care may be well positioned to manage patients with the most complex needs, there is a risk in specialists being called upon to see all patients with palliative care needs.…”
Section: Nursing and Palliative Care: A Critical Reflectionmentioning
confidence: 99%
“…As identified by participants here and elsewhere, inpatient social workers frequently learn palliative skills through observation and collaboration with specialist-level palliative social work colleagues (Sumser, Remke, Leimena, Altilio, & Otis-Green, 2015). Inpatient social workers HOSPITAL SOCIAL WORK GENERALIST PALLIATIVE SKILLS 20 with no prior palliative-related education at hospitals without a dedicated specialist-level palliative social worker could lack the necessary proximity for learning generalist-level palliative social work skills (Firn et al, 2016). Finally, institutional value for cycling patients through the hospital quickly, and inpatient social workers part in accomplishing that goal, could drive hiring practices and define social work scope of practice (Chan, Farias, Bambos, & Escobar, 2011;Lee et al, 2014;Lovett, Illg, & Sweeney, 2016).…”
Section: Education Practice and Research Implicationsmentioning
confidence: 99%